A waterproof coating for nanometer heat-reflecting photovoltaic roofing
Patent Information
- Application Number
- CN202411927724.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Existing roofing waterproofing materials exhibit shortcomings in terms of heat insulation, weather resistance, and weather resistance. In particular, existing roofing waterproofing materials are prone to aging in high-temperature environments, especially in summer, which affects the building's energy-saving effect. Furthermore, their performance is further reduced after the installation of photovoltaic modules.
A nano-heat-reflective waterproof coating is prepared by sintering a mixture of nano-powders such as lanthanum oxide, calcium oxide, boron oxide, and magnesium fluoride to create nano-microcrystalline stone. This nano-microcrystalline stone is then added to the polyurea waterproof coating to achieve a good reflective effect. The nano-microcrystalline stone is fully dispersed and combined in the waterproof coating, improving the heat insulation performance and solar reflectivity.
It improves the heat insulation, reflectivity and weather resistance of waterproof coatings, enhances photovoltaic power generation efficiency, and extends the service life of waterproof coatings.
Smart Images

Figure BDA0005209616020000081 
Figure BDA0005209616020000091
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of waterproof coatings, and in particular to a nano-heat reflective waterproof coating for photovoltaic roofs. Background Technology
[0002] Currently, most roof waterproofing materials on the market still use asphalt-based waterproof coatings or membranes. While asphalt-based waterproofing materials offer some waterproofing effect and can effectively prevent water penetration into the roof in the short term, their performance in terms of heat insulation, high-temperature resistance, and aging resistance is poor. Especially in the high temperatures of summer, asphalt-based waterproofing materials can easily lead to increased internal building temperatures and affect building energy efficiency. Furthermore, they are prone to aging and embrittlement under high temperatures and ultraviolet radiation, resulting in a decline in waterproofing performance.
[0003] With the vigorous development of the photovoltaic industry in recent years, more and more building roofs are being fitted with photovoltaic modules. However, when traditional waterproofing materials are applied to roofs with photovoltaic modules, their performance defects become more prominent. Firstly, the installation of photovoltaic modules may cause additional mechanical stress and vibration to the roof and the pre-laid waterproofing material, thus accelerating the aging and damage of the waterproofing material. Secondly, the photovoltaic modules generate a large amount of heat during long-term operation, which may cause serious thermal damage to the underlying waterproofing material, further reducing its waterproofing and heat insulation performance. Therefore, providing a waterproofing coating suitable for building roofs containing photovoltaic modules has significant market implications. Summary of the Invention
[0004] In order to improve the heat insulation effect and heat aging resistance of waterproof coatings, and make them more suitable for waterproofing construction of photovoltaic roofs, this application provides a nano-heat reflective waterproof coating for photovoltaic roofs.
[0005] Firstly, the nano-heat-reflective waterproof coating provided in this application adopts the following technical solution: A nano-heat reflective waterproof coating is made by mixing component A and component B in a mass ratio of 1:(1-2). Component A comprises the following raw materials in parts by weight: 4,4'-Dicyclohexylmethanediamine: 35-50 parts; Polyisocyanates: 50-65 parts; Component B comprises the following raw materials in parts by weight: Polyaspartic acid ester: 40-55 parts; Amino chain extender: 10-20 parts; Nanocrystalline stone: 15-20 parts; Titanium dioxide: 5-12 parts; Defoaming and leveling agent: 1.2-2 parts.
[0006] The nanocrystalline stone is prepared by fully mixing natural quartz sand, nano-mixed powder and binder in a mass ratio of (5-6):(3-4):1, and then sintering, grinding and sieving at high temperature; the nano-mixed powder includes lanthanum oxide and calcium oxide, and also includes one or more of boron oxide and magnesium fluoride; the binder is a mixture of polyvinyl alcohol aqueous solution and phosphoric acid in a mass ratio of (9-9.5):(0.5-1).
[0007] By employing the aforementioned technical solution, sintering and modifying natural quartz sand using a mixture of nanoparticles such as lanthanum oxide, calcium oxide, boron oxide, and magnesium fluoride, nanocrystalline stone with excellent reflective properties can be obtained. Furthermore, as the nanocrystalline stone is fully dispersed and combined in a polyurea-based waterproof coating, it forms a shielding effect within the coating, contributing to its superior heat insulation, solar reflectivity, and weather resistance. Simultaneously, the waterproof coating's high solar reflectivity allows it to be applied to the waterproofing of photovoltaic roofs. This allows the coating to not only provide waterproofing but also reflect sunlight onto the photovoltaic modules, thereby enhancing the frequency of photovoltaic power generation.
[0008] Optionally, the nano-mixed powder is a mixture of lanthanum oxide, calcium oxide, boron oxide and magnesium fluoride in a mass ratio of (8-10):(7-8):(1-3):1.
[0009] By adopting the above technical solution, the prepared nanocrystals have better reflective effect, which can further improve the effect on waterproof coatings, and make the waterproof coatings have higher heat insulation performance, reflective performance and weather resistance.
[0010] Optionally, the preparation method of the nanocrystalline stone includes the following steps: A1. The natural quartz sand and the nano-mixed powder are thoroughly mixed and ball-milled with water to obtain a mixed slurry. The mixed slurry is then dried, the binder is added, and the mixture is stirred evenly. After granulation, the mixed granules are obtained. The mixed granules are then placed in a self-sealing plastic bag and aged for no less than 1 day. After being taken out, they are dried again to obtain the initial material. A2. Heat the raw material to 650-700℃, maintain the temperature and calcine and degrease for 1-2 hours to obtain a rough blank; A3. Slowly heat the rough blank to 1380-1450℃, maintain the temperature and perform vacuum sintering for 3-4 hours. After sintering, allow it to cool naturally to room temperature in the furnace. Remove it and further crush, add water for ball milling, dry and sieve to obtain nano-microcrystalline stone with a particle size of less than 500nm.
[0011] By adopting the above technical solution, the preparation method is simple and convenient, which is conducive to large-scale industrial production.
[0012] Optionally, in the calcination and degreasing in step A2, inert gas needs to be circulated in advance, and the initial material is fed in after the furnace is filled with inert gas, and calcination and degreasing are carried out in an inert atmosphere; in the vacuum sintering and shaping in step A3, the vacuum degree in the furnace needs to be maintained at less than or equal to 15 kPa.
[0013] By adopting the above technical solution, the inert gas circulated during the calcination and degreasing process can effectively remove the waste gas generated by the binder during calcination, and also helps to stabilize the calcination and degreasing environment in the degreasing furnace, reducing the generation of side reactions. Similarly, in vacuum sintering and shaping, the vacuum environment can reduce adverse reactions such as oxidation and nitriding in the product, which is beneficial to and improves the sintering purity and sintering quality of the nanocrystalline stone.
[0014] Optionally, the nanocrystalline stone needs to undergo surface activation treatment before being added. The surface activation treatment of the nanocrystalline stone includes the following steps: First, the nanocrystalline stone is immersed in an acidic solution and heated to 55-60°C. The mixture is stirred and reacted for 5-10 minutes. The nanocrystalline stone is then washed using vacuum filtration until the washing liquid is neutral, resulting in acid-treated nanocrystalline stone. Next, the acid-treated nanocrystalline stone is immersed in a 2% γ-aminopropyltriethoxysilane solution for 20-30 minutes. After vacuum filtration, it is dried to obtain surface-activated nanocrystalline stone.
[0015] By adopting the above technical solution, the oxide impurities that are not fully melted and bonded in the nano-microcrystalline stone can be effectively removed. At the same time, the bonding strength between the nano-microcrystalline stone and polyurea can be improved, which is conducive to giving full play to the reinforcing and modifying effects of the nano-microcrystalline stone, and further improving the heat insulation performance, reflective performance and weather resistance of the waterproof coating.
[0016] Optionally, in component A, the polyisocyanate is one of hexamethylene diisocyanate or isophorone diisocyanate.
[0017] By adopting the above technical solution, both hexamethylene diisocyanate and isophorone diisocyanate belong to aliphatic diisocyanates. By reacting the polyurea semi-prepolymer prepared by aliphatic diisocyanate with polyaspartic acid ester, the curing speed of polyurea waterproof coating can be appropriately reduced to facilitate the full leveling of the waterproof coating. In addition, the tensile strength and elongation of the coating film can be improved, which is beneficial to improving the mechanical properties of the coating film.
[0018] Optionally, in component B, the amino chain extender is one of dimethylthiotoluene diamine or N,N'-dimethyl-p-diphenylamine.
[0019] By adopting the above technical solution, dimethylthiotoluene diamine and N,N'-dimethyl-p-diphenylamine are both sterically hindered primary amines. Through their high steric hindrance, the reactivity of the primary amines with polyisocyanates can be effectively controlled, thereby controlling the curing process of the waterproof coating and extending its curing time. This is beneficial for the waterproof coating to fully level and form a uniform and smooth waterproof film, which helps to improve the reflectivity of sunlight and enhance the heat insulation effect.
[0020] Optionally, the titanium dioxide is rutile titanium dioxide, and the defoaming and leveling agent is polyether-modified polydimethylsiloxane.
[0021] By adopting the above technical solutions, rutile titanium dioxide exhibits better weather resistance and hiding power compared to anatase titanium dioxide. It is not only less prone to yellowing and chalking, but also possesses high whiteness and excellent gloss. Combined with nanocrystalline stone, it further improves the weather resistance and thermal insulation performance of the waterproof coating. Simultaneously, the use of polyether-modified polydimethylsiloxane as a defoaming and leveling agent reduces the surface tension of the polyurea-based waterproof coating, allowing it to flow fully when sprayed onto the roof, thus forming a uniform and smooth waterproof film. This improves solar reflectivity and enhances thermal insulation.
[0022] Secondly, the nano-heat-reflective waterproof coating provided in this application adopts the following technical solution: A method for preparing a nano-heat-reflective waterproof coating includes the following steps: S1. Preparation of component A: 4,4'-dicyclohexylmethanediamine is heated to 105-110℃ for dehydration under reduced pressure. Dehydration is stopped when the water content is lower than 0.1%. The temperature is lowered to 85-88℃. Polyisocyanate is added dropwise while stirring at the same temperature, and the addition is completed within 2 hours. After the addition is completed, the temperature is maintained and the reaction is allowed to stand for 2-3 hours to obtain component A. S2. Preparation of component B: Polyaspartic acid ester, amino chain extender and titanium dioxide are thoroughly mixed, heated to 105-120℃ for dehydration under reduced pressure, then cooled to below 40℃, and defoaming and leveling agent is added. After thorough stirring, component B is obtained. S3. Preparation of waterproof coating: The prepared component A and component B are stored separately. Before use, component A and component B are thoroughly mixed in proportion to obtain a nano heat-reflective waterproof coating.
[0023] By adopting the above technical solution Thirdly, the application of the nano-heat-reflective waterproof coating provided in this application adopts the following technical solution: An application of a nano-heat reflective waterproof coating for the construction of waterproof coatings on photovoltaic roofs.
[0024] By adopting the above technical solution, the nano-heat-reflective waterproof coating with added nano-microcrystalline stone exhibits excellent reflectivity and a high solar reflectance. When applied to roof waterproofing coatings containing photovoltaic modules, it can fully reflect sunlight onto the photovoltaic modules, thereby enhancing photovoltaic power generation efficiency. Furthermore, the nano-heat-reflective waterproof coating with added nano-microcrystalline stone also possesses good heat insulation and weather resistance properties, which helps reduce the adverse effects of photovoltaic modules on the waterproof coating and extends its service life.
[0025] In summary, the technical solution of this application has at least one of the following beneficial effects.
[0026] 1. By sintering and modifying natural quartz sand using a mixture of nano-powders such as lanthanum oxide, calcium oxide, boron oxide, and magnesium fluoride, nanocrystalline stone with good reflective properties can be obtained. Furthermore, as the nanocrystalline stone is fully dispersed and combined in polyurea-based waterproof coatings, it helps to give the waterproof coatings good heat insulation performance, solar reflectivity, and weather resistance.
[0027] 2. Due to the high solar reflectivity of waterproof coatings, they can be applied to the waterproofing of photovoltaic roofs. In this way, while providing waterproofing, the coatings can also reflect sunlight onto the photovoltaic modules, which helps to enhance the frequency of photovoltaic power generation. Detailed Implementation
[0028] The present application will be further described in detail below with reference to preparation examples, embodiments and comparative examples.
[0029] Polyaspartic acid ester is specifically prepared by Michael addition of diethyl maleate and polyetheramine, and the specific brand of polyetheramine is Jeffamine D230.
[0030] The titanium dioxide was specifically purchased from Panzhihua Iron and Steel Group Co., Ltd., and the grade was R-248 rutile titanium dioxide.
[0031] The defoaming and leveling agent was specifically purchased from BYK Chemical, brand name BKY-331.
[0032] Preparation Example
Preparation Example 1
[0033] The nano-mixed powder is specifically a mixture of lanthanum oxide, calcium oxide, and boron oxide in a mass ratio of 10:8:2, meaning the nano-mixed powder comprises 4.5 kg of lanthanum oxide, 3.6 kg of calcium oxide, and 0.9 kg of boron oxide. The binder is specifically a mixture of polyvinyl alcohol aqueous solution and phosphoric acid in a mass ratio of 9.5:0.5, meaning the binder comprises 2.85 kg of polyvinyl alcohol aqueous solution and 0.15 kg of phosphoric acid. Specifically, in this preparation example, the concentration of the polyvinyl alcohol aqueous solution is 5%.
[0034] A nanocrystalline stone is prepared by the following method: A1. Natural quartz sand and nano-mixed powder are thoroughly mixed and ball-milled with water. After ball milling, a mixed slurry is obtained. The mixed slurry is dried, and then a binder is added. After stirring evenly, the mixture is granulated to obtain mixed granules. The mixed granules are then placed in self-sealing plastic bags and aged for 1 day. After being taken out, they are dried again to obtain the initial material.
[0035] A2. The raw material is fed into a degreasing furnace, heated to 650℃, and maintained at that temperature for 2 hours for calcination and degreasing. The resulting rough blank is then removed. Nitrogen gas is circulated into the degreasing furnace at a flow rate of 70L / min. Once the furnace is filled with nitrogen, the raw material is fed back into the furnace and calcined and degreased in a nitrogen atmosphere.
[0036] A3. The rough blank is fed into a vacuum sintering furnace and slowly heated to 1420℃ over 3 hours. The temperature is maintained, and vacuum sintering is performed for 3 hours to set the shape. After sintering, the blank is allowed to cool naturally to room temperature. It is then removed and further pulverized, ball-milled with water, dried, and sieved to obtain nanocrystalline stone with a particle size of less than 500nm. The vacuum sintering furnace must maintain a vacuum level of less than or equal to 15KPa.
[0037] In the water-adding ball milling process of steps A1 and A3, the mass ratio of material to milling balls is 1:2:1.
[0038]
Preparation Example 2
[0039] The nano-mixed powder is specifically a mixture of lanthanum oxide, calcium oxide, boron oxide, and magnesium fluoride in a mass ratio of 8:8:3:1, meaning the nano-mixed powder contains 3.6 kg of lanthanum oxide, 3.6 kg of calcium oxide, 1.35 kg of boron oxide, and 0.45 kg of magnesium fluoride. The binder is specifically a mixture of polyvinyl alcohol aqueous solution and phosphoric acid in a mass ratio of 9:1, meaning the binder specifically contains 2.7 kg of polyvinyl alcohol aqueous solution and 0.3 kg of phosphoric acid. Specifically, in this preparation example, the concentration of the polyvinyl alcohol aqueous solution is 5%.
[0040] A nanocrystalline stone is prepared by the following method: A1. Natural quartz sand and nano-mixed powder are thoroughly mixed and ball-milled with water. After ball milling, a mixed slurry is obtained. The mixed slurry is dried, and then a binder is added. After stirring evenly, the mixture is granulated to obtain mixed granules. The mixed granules are then placed in self-sealing plastic bags and aged for 1 day. After being taken out, they are dried again to obtain the initial material. A2. The raw material is fed into a degreasing furnace, heated to 700℃, maintained at the temperature, and calcined for degreasing for 1 hour. The resulting rough blank is then removed. Nitrogen gas is circulated into the degreasing furnace at a flow rate of 95L / min. Once the degreasing furnace is filled with nitrogen, the raw material is fed back into the degreasing furnace and calcined for degreasing in a nitrogen atmosphere.
[0041] A3. The rough blank is fed into a vacuum sintering furnace and slowly heated to 1380℃ over 3 hours. The temperature is maintained, and vacuum sintering is performed for 4 hours to set the shape. After sintering, the blank is allowed to cool naturally to room temperature. It is then removed and further pulverized, ball-milled with water, dried, and sieved to obtain nanocrystalline stone with a particle size of less than 500nm. The vacuum sintering furnace must maintain a vacuum level of less than or equal to 15KPa.
[0042] In the water-adding ball milling process in steps A1 and A3, the mass ratio of material, milling balls, and water is 1:2:1.
[0043]
Preparation Example 3
[0044] In this preparation example, the nano-mixed powder specifically consists of lanthanum oxide, calcium oxide, and magnesium fluoride, and the mass ratio of lanthanum oxide, calcium oxide, and magnesium fluoride is 10:8:2, that is, the nano-mixed powder includes 4.5 kg of lanthanum oxide, 4.05 kg of calcium oxide, and 0.45 kg of magnesium fluoride.
[0045]
Preparation Example 4
[0046] In this preparation example, the nano-mixed powder is specifically composed of lanthanum oxide, calcium oxide, boron oxide, and magnesium fluoride in a mass ratio of 10:9:1:1, that is, the nano-mixed powder includes 4.5 kg of lanthanum oxide, 4.05 kg of calcium oxide, 3.6 kg of boron oxide, and 0.45 kg of magnesium fluoride.
[0047]
Preparation Example 5
[0048] In this preparation example, the nano-mixed powder specifically comprises lanthanum oxide, calcium oxide, boron oxide, and magnesium fluoride, and the mass ratio of lanthanum oxide, calcium oxide, and magnesium fluoride is 10:8:2:1, that is, the nano-mixed powder includes 4.5 kg of lanthanum oxide, 3.15 kg of calcium oxide, 0.9 kg of boron oxide, and 0.45 kg of magnesium fluoride. Example
[0049]
Example 1
[0050] Component A consists of 35 kg of 4,4'-dicyclohexylmethanediamine and 50 kg of hexamethylene diisocyanate. Component B consists of 40 kg of polyaspartic acid ester, 20 kg of amino chain extender, 20 kg of nanocrystalline stone, 5 kg of titanium dioxide, and 1.2 kg of defoaming and leveling agent.
[0051] Specifically, in component B, the amino chain extender is dimethylthiotoluene diamine, and the nanocrystalline stone is a type of nanocrystalline stone prepared in [Preparation Example 1].
[0052] A method for preparing a nano-heat-reflective waterproof coating includes the following steps: S1. Preparation of component A: 4,4'-dicyclohexylmethanediamine was heated to 110°C and dehydrated under reduced pressure. When its water content was less than 0.1%, the dehydration was stopped, the temperature was lowered to 85°C, and hexamethylene diisocyanate was added dropwise while stirring at the same temperature. The addition was completed within 2 hours. After the addition was completed, the temperature was maintained and the reaction was allowed to stand for 2 hours to obtain component A. S2. Preparation of component B: Polyaspartic acid ester, amino chain extender and titanium dioxide are thoroughly mixed and heated to 110°C for dehydration under reduced pressure. Then the temperature is lowered to 40°C, and defoaming and leveling agent is added. After thorough stirring, component B is obtained. S3. Preparation of waterproof coating: The prepared components A and B are stored separately. Before use, components A and B are thoroughly mixed at a mass ratio of 1:1 to obtain a nano heat-reflective waterproof coating.
[0053] An application of a nano-heat reflective waterproof coating for the construction of waterproof coatings on photovoltaic roofs.
[0054]
Example 2
[0055] Component A consists of 40 kg of 4,4'-dicyclohexylmethanediamine and 65 kg of isophorone diisocyanate. Component B consists of 55 kg of polyaspartic acid ester, 10 kg of amino chain extender, 15 kg of nanocrystalline stone, 12 kg of titanium dioxide, and 2 kg of defoaming and leveling agent.
[0056] Specifically, in component B, the amino chain extender is N,N'-dimethyl-p-diphenylamine, and the nanocrystalline stone is a type of nanocrystalline stone prepared in [Preparation Example 2].
[0057] A method for preparing a nano-heat-reflective waterproof coating includes the following steps: S1. Preparation of component A: 4,4'-dicyclohexylmethanediamine was heated to 105°C and dehydrated under reduced pressure. When its water content was less than 0.1%, the dehydration was stopped, the temperature was lowered to 88°C, and isophorone diisocyanate was added dropwise while stirring at the same temperature. The dropwise addition was completed within 2 hours. After the dropwise addition was completed, the temperature was maintained and the reaction was allowed to stand for 3 hours to obtain component A. S2. Preparation of component B: Polyaspartic acid ester, amino chain extender and titanium dioxide are thoroughly mixed and heated to 105°C for dehydration under reduced pressure. Then the temperature is lowered to 40°C, and defoaming and leveling agent is added. After thorough stirring, component B is obtained. S3. Preparation of waterproof coating: The prepared components A and B are stored separately. Before use, components A and B are thoroughly mixed at a mass ratio of 1:2 to obtain a nano heat-reflective waterproof coating.
[0058] An application of a nano-heat reflective waterproof coating for the construction of waterproof coatings on photovoltaic roofs.
[0059]
Example 3
[0060] In this embodiment, the nanocrystalline stone specifically selected is a nanocrystalline stone prepared in [Preparation Example 3].
[0061]
Example 4
[0062] In this embodiment, the nanocrystalline stone specifically selected is the nanocrystalline stone prepared in [Preparation Example 4].
[0063]
Example 5
[0064] In this embodiment, the nanocrystalline stone specifically selected is a nanocrystalline stone prepared in [Preparation Example 5].
[0065]
Example 6
[0066] Comparative Example Comparative Example 1 A waterproof coating, which differs from [Example 1] in that it does not contain nanocrystalline stone.
[0067] In this comparative example, nanocrystalline stone was replaced in equal amounts with natural quartz sand with a particle size of less than 500 nm.
[0068] Performance testing 1. Thermal insulation test: The test was conducted according to Appendix B of GB / T 25261-2018 Reflective Thermal Insulation Coatings for Buildings, and the thermal insulation temperature difference ΔT between the waterproof coatings prepared in each example and comparative example and the reference blackboard was recorded. The test sample and the reference blackboard were also prepared according to Section 3 of Appendix B of GB / T 25261-2018 Reflective Thermal Insulation Coatings for Buildings.
[0069] 2. Solar reflectance: The test was conducted in accordance with Section 6.4 of GB / T 25261-2018 Reflective Thermal Insulation Coatings for Buildings, and the solar reflectance of the waterproof coatings prepared in each example and comparative example was recorded.
[0070] 1. Aging Resistance Test: First, prepare the coating film according to Section 4 of GB / T 16777-2008 Test Methods for Waterproof Coatings for Buildings, and perform sufficient curing according to Table 1. Then, conduct the test according to Section 9.2.6 of GB / T 16777-2008 Test Methods for Waterproof Coatings for Buildings, and calculate and record the retention rate (%) of tensile properties before and after artificial climate aging for each example and comparative example.
[0071] Table 1. Partial Performance Test Data of Waterproof Coating Based on the data from Example 1, Comparative Example 1, and Table 1, it can be seen that under the same polyurea waterproof coating system, Example 1, by using lanthanum oxide, calcium oxide, boron oxide, and natural quartz sand for sintering modification to form nanocrystalline stone, effectively improves the thermal insulation performance and solar reflectivity of the polyurea waterproof coating compared to the natural quartz sand added in Comparative Example 1. It also improves the weather resistance of the waterproof coating. This may be because the sintering modification of natural quartz sand with lanthanum oxide, calcium oxide, and boron oxide increases the crystalline phase content of the nanocrystalline stone, giving it a good reflective effect. Furthermore, as the nanocrystalline stone is fully dispersed and combined in the coating, it forms a shielding effect, thereby achieving the purpose of reflecting sunlight and resisting heat aging. Simultaneously, it reduces the thermal conductivity of the waterproof coating and improves its thermal insulation effect.
[0072] Based on the data from Examples 1 and 3-5, as well as Table 1, it can be seen that when the nano-mixed powder in the nano-microcrystalline stone is composed of lanthanum oxide, calcium oxide, boron oxide, and magnesium fluoride mixed in a certain proportion, the improvement effect of the nano-microcrystalline stone on waterproof coatings can be further enhanced.
[0073] Based on the data from Examples 5 and 6 and Table 1, it can be seen that surface activation treatment of nanocrystalline stone can further improve its effect on waterproof coatings, resulting in better thermal insulation, reflective properties, and weather resistance. This may be because acid treatment and aminosilane modification not only remove incompletely fused oxide impurities from the nanocrystalline stone but also improve the bonding strength between the nanocrystalline stone and polyurea. This, in turn, helps to fully utilize the reinforcing and modifying effects of the nanocrystalline stone, further enhancing the thermal insulation, reflective properties, and weather resistance of the polyurea waterproof coating.
[0074] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this specific embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A nano-heat-reflective waterproof coating, characterized in that, It is composed of component A and component B mixed in a mass ratio of 1:(1-2); Component A comprises the following raw materials in parts by weight: 4,4'-Dicyclohexylmethanediamine: 35-50 parts; Polyisocyanates: 50-65 parts; Component B comprises the following raw materials in parts by weight: Polyaspartic acid ester: 40-55 parts; Amino chain extender: 10-20 parts; Nanocrystalline stone: 15-20 parts; Titanium dioxide: 5-12 parts; Defoaming and leveling agent: 1.2-2 parts; The nanocrystalline stone is prepared by fully mixing natural quartz sand, nano-mixed powder and binder in a mass ratio of (5-6):(3-4):1, and then sintering, grinding and sieving; the nano-mixed powder is a mixture of lanthanum oxide, calcium oxide, boron oxide and magnesium fluoride in a mass ratio of (8-10):(7-8):(1-3):1, and the binder is a mixture of polyvinyl alcohol aqueous solution and phosphoric acid in a mass ratio of (9-9.5):(0.5-1); The preparation method of the nanocrystalline stone includes the following steps: A1. The natural quartz sand and the nano-mixed powder are thoroughly mixed and ball-milled with water to obtain a mixed slurry. The mixed slurry is then dried, the binder is added, and the mixture is stirred evenly. After granulation, the mixed granules are obtained. The mixed granules are then placed in a self-sealing plastic bag and aged for no less than 1 day. After being taken out, they are dried again to obtain the initial material. A2. Heat the raw material to 650-700℃, maintain the temperature and calcine and degrease for 1-2 hours to obtain a rough blank; A3. Slowly heat the rough blank to 1380-1450℃, maintain the temperature and perform vacuum sintering for 3-4 hours. After sintering, allow it to cool naturally to room temperature in the furnace. Remove it and further crush, add water for ball milling, dry and sieve to obtain nano-microcrystalline stone with a particle size of less than 500nm.
2. The nano-heat-reflective waterproof coating according to claim 1, characterized in that: In the calcination and degreasing process of step A2, inert gas needs to be circulated in advance. After the furnace is filled with inert gas, the initial material is fed in and calcined and degreased in an inert atmosphere. In the vacuum sintering and shaping process of step A3, the vacuum degree in the furnace needs to be maintained at less than or equal to 15 kPa.
3. The nano-heat-reflective waterproof coating according to claim 1, characterized in that: The nanocrystalline stone needs to undergo surface activation treatment before being added. The surface activation treatment of the nanocrystalline stone includes the following steps: First, the nanocrystalline stone is immersed in an acidic solution and heated to 55-60℃. The mixture is stirred and reacted for 5-10 minutes. The nanocrystalline stone is then washed by vacuum filtration until the washing liquid is neutral, resulting in acid-treated nanocrystalline stone. The acid-treated nanocrystalline stone is then immersed in a 2% γ-aminopropyltriethoxysilane solution for 20-30 minutes. After vacuum filtration, the solution is dried to obtain surface-activated nanocrystalline stone.
4. The nano-heat-reflective waterproof coating according to claim 1, characterized in that: In component A, the polyisocyanate is one of hexamethylene diisocyanate or isophorone diisocyanate.
5. The nano-heat-reflective waterproof coating according to claim 1, characterized in that: In component B, the amino chain extender is one of dimethylthiotoluene diamine or N,N'-dimethyl-p-diphenylamine.
6. The nano-heat-reflective waterproof coating according to claim 1, characterized in that: The titanium dioxide is rutile titanium dioxide, and the defoaming and leveling agent is polyether-modified polydimethylsiloxane.
7. A method for preparing a nano-heat-reflective waterproof coating, used to prepare a nano-heat-reflective waterproof coating as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Preparation of component A: 4,4'-dicyclohexylmethanediamine is heated to 105-110℃ for dehydration under reduced pressure. Dehydration is stopped when the water content is lower than 0.1%. The temperature is lowered to 85-88℃. Polyisocyanate is added dropwise while stirring at the same temperature, and the addition is completed within 2 hours. After the addition is completed, the temperature is maintained and the reaction is allowed to stand for 2-3 hours to obtain component A. S2. Preparation of component B: Polyaspartic acid ester, amino chain extender and titanium dioxide are thoroughly mixed, heated to 105-120℃ for dehydration under reduced pressure, then cooled to below 40℃, and defoaming and leveling agent is added. After thorough stirring, component B is obtained. S3. Preparation of waterproof coating: The prepared component A and component B are stored separately. Before use, component A and component B are thoroughly mixed in proportion to obtain a nano heat-reflective waterproof coating.
8. An application of a nano-heat-reflective waterproof coating, applicable to the nano-heat-reflective waterproof coating as described in any one of claims 1-6, characterized in that: It is used in the construction of waterproof coatings for photovoltaic roofs.
Citation Information
Patent Citations
Formulation of imperforate micro-spar sheet material and manufacturing method thereof
CN101265027A
Waterproof coating, preparation method thereof and waterproof system containing same as well as construction method
CN108034347A
